Gamma/delta T cells in patients with acute brucellosis - Kilic, S. S.; Akbulut, H. H.; Ozden, M.; Bulut, V. (Springer-Verlag Italia Srl, 2009)
We aimed to investigate the population of gamma/delta T (gamma/delta T) cells in patients with acute brucellosis. When the bacteria penetrate to the host, the innate immune response aims to prevent the attack by non-activated professional phagocytes. At that moment, macrophages trigger the other cells of the immune system. The cells that can respond immediately are natural killer and gamma/delta T cells. The study included 40 cases of acute brucellosis and 20 healthy volunteers. In this study, it was aimed to compare gamma/delta and alpha/beta (alpha/beta) receptors of the T cells at pre- and post treatment period of patients diagnosed as brucellosis, especially to evaluate the levels of gamma/delta T cells at monitoring of the disease, using flow cytometry. As a result, it was observed that gamma/delta T cells significantly increased in peripheral blood in patients with brucellosis compared with the healthy individuals (13.23 +/- A 4.7 and 5.25 +/- A 1.4, respectively (p = 0.0001)). gamma/delta T cells were significantly decreased after the brucellosis treatment (p < 0.01). The results of the present study indicate that considerable counts of gamma/delta T cells are involved in acute brucellosis cases. Our findings suggest that gamma/delta TCR bearing cell counts may be used as a supplementary marker for monitoring brucellosis.
Keywords: Brucellosis; Gamma/delta T cells